Searching for Symbolic Value of Cattle: Tropical Livestock Units, Market Price, and Cultural Value of Maasai Livestock - Robert J. Quinlan; Isaya Rumas; Godfrey Naiskye; Marsha Quinlan; Jonathan Yoder (Ethnobiology Letters, 2016)
We examine metabolic, market, and symbolic values of livestock relative to cultural “positioning” by gender, marriage, and household production among Maasai people in Simanjiro, Tanzania to assess local “proximate currencies” relevant for “cultural success.” Data from mixed methods ethnographic research include qualitative interviews since 2012, observation of 85 livestock market sales in 2013 and 2015, and 37 short key informant interviews in 2015. We examine fit between market values, Tropical Livestock Units (TLU, weight-based species exchange ratio), and perceived value from interviews for moran (unmarried men), muruo (married men), and tɔmɔnɔ́k (married women). Hedonic regression using livestock species, sex, maturity, and size accounted for 90% of the local market price of livestock. We compared the market-based exchange ratio between cattle and smallstock (sheep and goats) to TLU and perceived values situating symbolic value of cattle in terms of Maasai household production schema. One TLU model accurately predicted market exchange ratios, while another predicted hypothetical exchanges, suggesting need for improved livestock wealth estimation for pastoralists. Ritual context, subsistence work, and cultural position influenced perceived values: Moran overvalued cattle by 100% of the local market value. Tɔmɔnɔ́k accurately perceived the market exchange ratio despite never directly engaging in livestock market transactions. Muruo perceived exchange ratios intermediate between moran and tɔmɔnɔ́k. We argue that these perceptions of value reflect distinct labor responsibilities of moran, muruo, and tɔmɔnɔ́k in livestock management, differential value of bridewealth, and control of meat and milk.Attention to value of different livestock species in cultural models of production may prove useful for development efforts.